Galactic and extra-galactic radio astronomy - 5282 United States. National Radio Astronomy Observatory, Green Bank, West Virginia; Verschuur, Gerrit L.; Kellermann, Kenneth I., 1937- (New York : Springer-verlag, 1974)
26